AUDITING TEACHING METHODS. - Davies, E. C. (The Accounting Review, 1935)
Abstract In any consideration or discussion of the methods of teaching in Auditing it would seem that the question of paramount importance, or at least the one causing the most difficulty, is what might be called one of realism or practicability and the developing in the student of the feeling that the course is not just a theoretical course but that it is tangible and practical and has a direct relationship to actual business procedure. There is no particular difficulty in connection with text material covering the theory of auditing. There is an overabundance of printed material explaining what to do in the course of any type of audit engagement, although much of this material consists principally of statements as to what the auditor should do. The chief difficulty is in giving the students an understanding and appreciation of the practical problems of audit procedure and the developing of a sense of realism in the course and in the work. The ideal and most satisfactory method of handling the situation would be to have actual accounting records and to have a wide enough selection to illustrate the variations in form and procedure that would be encountered in actual business and a sufficient number of sets of books so that students could work on these records individually under the supervision of the instructor.